Pemanfaatan Web Profile sebagai Media Promosi Pada UMKM Fresh Laundry - Arumsari; Saly Kurnia Octaviani; Cinthia Annisa Vinahapsari3 (Jurnal Pengabdian Masyarakat Teknologi dan Pendidikan (MANTAP), 2024)
Fresh Laundry is a laundry service business located in Ponowaren, Tawangsari, Sukoharjo. This community service focuses on utilizing a web profile to develop the business of Fresh Laundry so that it can reach all regions. The method used in this research are interviews, observation and documentation.  The web profile applied to this business contains facilities, as well as services available at the Fresh Laundry business. This Web Profile also displays several summaries of activities in this Fresh Laundry business so that this can attract customers to promote the fresh laundry business.